The gene fl(2)D is required for various Sxl-controlled processes in Drosophila females. - Granadino, B.; Sanjuan, A.B.; Sanchez, L. (Roux's Archives of Developmental Biology, 1991)
In Drosophila melanogaster, the gene Sex-lethal (Sxl) controls the processes of sex determination, dosage compensation, oogenesis and sexual behaviour. The control of Sxl is by alternative splicing of its primary RNA. We have identified a gene, female-lethal-2-d (fl(2)d), which is needed for the female-specific splicing of Sxl RNA and which also has a vital function independent of Sxl. Here we analyse other aspects of the gene fl(2)d. Specifically, we have analysed the effect of the temperature-sensitive mutation fl(2)d (1) on the viability of adult flies homozygous for this mutation. We have found that the viability of the mutant females is reduced, while that of the mutant males is not affected. In addition, the capacity of the mutant females to be inseminated is considerably reduced, whilst all the mutant males are able to inseminate females. These effects on females are suppressed by Sxl (M1). However, the fat body cells of fl(2)d (1) homozygous females are able to synthesize yolk proteins at the restrictive temperature. We have also carried out, in males, a clonal analysis of fl(2)d (2), a mutation lethal in both sexes. We have found that the clones are fully viable. We conclude that the gene fl(2)d seems to be necessary during the adult life of females for the processes that require Sxl (+) activity. Moreover, the Sxl-independent vital function of fl(2)d seems to be required in both sexes only during larval development.